MASA and apartheid : the role of the institutionally organised South African medical profession in response to human rights violations within the Apartheid era, with special emphasis on the response of the Medical Association of South Africa (MASA) to the death of Steve Biko - Damster, Gavin Paul (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Phil.) -- University of Stellenbosch, 1998.